2011
DOI: 10.1080/15567030903030682
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Leaching on Sulfur and Mineral Matter Removal from Asphaltite (Harbul, SE Anatolia, Turkey)

Abstract: Desulfurization and demineralization by an aqueous caustic leaching method was investigated of an asphaltite sample from Harbul (Silopi, SE Anatolia, Turkey). The effects of different parameters, such as alkali concentration, time, and temperature, on the leaching efficiency were detailed and the experimental results are presented here. The caustic concentration varied from 0.1-1.0 M, temperature was 100-180 ı C, and leaching time varied from 4-16 h. The removal of total sulfur and ash increases with increasin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 30 publications
2
4
0
Order By: Relevance
“…Assam coal and concluded that effective deashing and desulfurization could be achieved at 95°C with caustic solution treatments. The aqueous caustic leaching has also been reported by Saydut et al (2011) where a Turkish asphaltite sample was treated under varying conditions with aqueous NaOH solution from 0.1 to 1 M concentration with variations in temperature from 100 to 180°C and time 4-16 h. The ash content of the asphaltite reduced from 32.49% to 18% and the total sulfur also dropped to 2.68% from 7.02%.…”
Section: Use Of Alkalis For Demineralisation Of Coalssupporting
confidence: 59%
“…Assam coal and concluded that effective deashing and desulfurization could be achieved at 95°C with caustic solution treatments. The aqueous caustic leaching has also been reported by Saydut et al (2011) where a Turkish asphaltite sample was treated under varying conditions with aqueous NaOH solution from 0.1 to 1 M concentration with variations in temperature from 100 to 180°C and time 4-16 h. The ash content of the asphaltite reduced from 32.49% to 18% and the total sulfur also dropped to 2.68% from 7.02%.…”
Section: Use Of Alkalis For Demineralisation Of Coalssupporting
confidence: 59%
“…The demineralization of coal with aqueous alkaline solution is reported by several researchers [149][150][151]. Kara and Ceylan [149] have reported similar results for demineralization (91%) of Turkish lignites with NaOH.…”
Section: Alkali Leachingsupporting
confidence: 69%
“…Kara and Ceylan [149] have reported similar results for demineralization (91%) of Turkish lignites with NaOH. The effect of aqueous caustic leaching (ACL) of asphaltite from Turkey was investigated by Saydut et al [151]. Caustic leaching (1 M NaOH) at 180 1C for 16 h reduced the ash content of asphaltite by 44.6%, pyritic sulfur by 83.3%, organic sulfur by 53.9%, total sulfur by 61.82% and volatile matter by 46.29%.…”
Section: Alkali Leachingmentioning
confidence: 99%
“…2NaOH+R-S→R-SNa 2 (11) Numerous researchers [62][63] stated the demineralization of coal with an aqueous alkali solution. Wang et al, (1986) investigated that the removal of mineral matter from Miler Blend (high ash, 15.5%) and Wandon (low ash, 7%) coal of Australia by treatment with the alkali solution at 460 K. The researchers showed that it is easier to reduce mineral rich components like quartz and kaolinite by alkali treatment although the elimination of Ca and Fe bearing mineral depends on the type of composition in coal [64].…”
Section: Alkali Leachingmentioning
confidence: 99%